Construction and Analysis of circRNA-miRNA-mRNA Molecular Regulatory Networks During Herba Gelsemium elegans Intoxication - Wang, Yinghao; Wu, Shuisheng; Yang, Ce; Gao, Hanyun; Yu, Hongmin; Lu, Xuehua; Yuan, Shugang (Frontiers in Pharmacology, 2019)
Gelsemium elegans (Gardner & Champ.) Benth. (GE) has therapeutic effects for pain and malignant tumors but also has high toxicity. Its mechanism of toxicity has not yet been fully clarified, thus limiting its application. Meanwhile, evidence has shown that circRNAs are closely related to the progression of disease. However, very little is known about their expression profiles during intoxication. In this paper, circRNA/mRNA microarrays were respectively performed to detect their expression profiles in mice with acute GE intoxication versus normal controls. CircRNAs were verified by qRT-PCR in subsequent experiments. A regulation pattern of circRNA→miRNA→mRNA was deduced based on intersection analysis of circRNA/mRNA microarrays. The results revealed circRNAs (143) and mRNAs (1,921) were significantly expressed during intoxication. Most of the circRNAs were exonic, and most distributions in chromosomes were transcribed from chr1, chr2, chr7, and chr11. Furthermore, dysregulated expression of mmu-circRNA-013703 and mmu-circRNA-010022 was verified. Then a circRNA-targeted miRNA-mRNA co-expression network was constructed. The network map contained 2 circRNAs, 52 miRNAs, and 752 mRNAs. GO & KEGG analysis further predicted that mmu-circRNA-013703 and mmu-circRNA-010022 may participate in cellular survival/demise-related, neuron/synapse-related and channel-related pathways. Based on functional modules analysis, a new network was formed, in which mmu-circRNA-013703 VS mmu-miR-361-3p linked to most mRNAs. Most of these mRNAs were known to be involved in the aforementioned functional module. This indicated that mmu-circRNA-013703 functioned as a sponge of miRNAs to regulate the more comprehensive circRNA-miRNA-mRNA co-expression network. Our approach revealed a landscape of dysregulated circRNA-miRNA-mRNA and may be valuable for the identification of new biomarkers during intoxication.